2017
DOI: 10.1016/j.athoracsur.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Elective Early Primary Repair of Tetralogy of Fallot: Analysis of Intermediate Term Outcomes

Abstract: Elective repair in patients greater than 55 days of age, irrespective of size of the patient, can be safely performed without any increase in reintervention rates. Both residual peak RVOT gradient and TPS are effective in identifying patients at increased risk of reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Controversy exists between authors who suggest that a total complete repair should be performed during the first 4 to 6 weeks of age, regardless of clinical presentation and anatomic findings [4,17]; however, some other authors promote the use of systemic-to-pulmonary shunts or a right ventricular outflow tract stent in very symptomatic neonates before the total repair, showing similar outcomes to total repair strategies [5,18].…”
Section: Commentmentioning
confidence: 99%
“…Controversy exists between authors who suggest that a total complete repair should be performed during the first 4 to 6 weeks of age, regardless of clinical presentation and anatomic findings [4,17]; however, some other authors promote the use of systemic-to-pulmonary shunts or a right ventricular outflow tract stent in very symptomatic neonates before the total repair, showing similar outcomes to total repair strategies [5,18].…”
Section: Commentmentioning
confidence: 99%
“…Cunningham et al showed that surgeries in tetralogy of Fallot patients older than 55 days were safe. 16 A study in Pakistan by Memon et al showed that mean age 9.39 ± 2.3 months had good outcomes after tetralogy of Fallot repair. 17 Baseline saturation <75% was an independent risk factor for low cardiac output syndrome and prolonged intubation.…”
Section: Discussionmentioning
confidence: 99%
“…If oxygen saturations are adequate, infants are discharged home on medications such as propranolol (to improve arterial oxygen saturations), which allows time for the pulmonary arteries to grow prior to surgery (Hoffman, ). Surgical intervention patching the VSD and enlarging the pulmonary valve is done between 2 and 6 months of age (Cunningham et al, ).…”
Section: Congenital Heart Diseasementioning
confidence: 99%